24:6+[23×(10-6-3)]+10=
Răspunsuri la întrebare
Răspuns de
2
24 : 6 + [ 23 × ( 10 - 6 - 3 ) ] + 10 =
24 : 6 + [ 23 × ( 4 - 3 ) ] + 10 =
24 : 6 + ( 23 × 1 ) + 10 =
24 : 6 + 23 + 10 =
4 + 23 + 10 =
27 + 10 =
= 37
24 : 6 + [ 23 × ( 4 - 3 ) ] + 10 =
24 : 6 + ( 23 × 1 ) + 10 =
24 : 6 + 23 + 10 =
4 + 23 + 10 =
27 + 10 =
= 37
Răspuns de
0
1.10 -6 =4
2.4-3=1
3.23×1=23
4.24:6=4
5.4+23=27
6.27+10=37
2.4-3=1
3.23×1=23
4.24:6=4
5.4+23=27
6.27+10=37
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă